Modeling the relationship between attachment styles and somatic symptoms with the mediating role of emotional processing - Mozhgan Falahatdoost; Behrouz Dolatshahi; Abbas Pourshahbaz; Mahmoud Dehghani; Mohsen Nouri Yalguzaghaji; Zahra Mohammadi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: In spite of our general knowledge about psychological roots and defects of developmental processes in the formation of somatic symptoms, the effect of the interaction of developmental components with cognitive-emotional variables is unclear. Previous researches suggest that individuals with insecure attachment may have a higher risk to experience of somatic symptoms. The main aim of this study is "Modeling the Relationship between Attachment Styles and Somatic Symptoms with the Mediating Role of Emotional Processing." MATERIALS AND METHODS: This study was a descriptive-correlational study. Two hundred and twenty individuals aged 18-59 years living in Tehran were selected by available sampling from the general population. Collins and Reed's Adult Attachment Scale, Baker's Emotional Processing Scale, and Patient Health Questionnaire were used to collecting data. Data analysis was performed by Pearson correlation and independent t-test. The conceptual model presented in this study was tested with a path analysis approach. RESULTS: Given the Chi-squared size (χ2 = 1.214; P > 0.05), it can be said that the proposed conceptual model fits well with the observed model. Besides, checking the other absolute and relative indices also shows a very good fit of the model. CONCLUSION: Our results showed that when the reciprocal effects of attachment styles were controlled, secure attachment could be considered as a protective factor against deficits in emotional processing and somatization of negative emotions. On the other hand, we found that when the dominant attachment style in individuals was anxiety based, it could be possible that they experience deficiency in the processing of emotion and more severe somatic symptoms.